Cover Picture: Engineering SpyCatcher Variants with Proteolytic Sites for Less‐Trace Ligation (Chin. J. Chem. 2/2019). Issue 2 (14th January 2019) - Zhang, Xue‐Jian; Wu, Xia‐Ling; Liu, Dong; Da, Xiao‐Di; Wang, Xiao‐Wei; Yang, Shuguang; Zhang, Wen‐Bin
Abstract : The cover picture shows an approach toward less‐trace SpyTag‐SpyCatcher ligation. A proteolytic recognition sequence has been engineered into the second loop of SpyCatcher to produce SpyCatcher DDDDK variant. The reaction between SpyTag and SpyCatcher DDDDK is highly efficient both in vivo and in vitro, producing a stable covalent complex. The complex can be further cleaved at the second loop by enterokinase, resulting in only a small scar after ligation. This protocol adds to the expanding toolbox of genetically‐encoded peptide‐protein chemistry for protein topology engineering. More details are discussed in the article by Zhang et al. on page 113–118. Abstract : The cover picture shows an approach toward less‐trace SpyTag‐SpyCatcher ligation. A proteolytic recognition sequence has been engineered into the second loop of SpyCatcher to produce SpyCatcher DDDDK variant. The reaction between SpyTag and SpyCatcher DDDDK is highly efficient both in vivo and in vitro, producing a stable covalent complex. The complex can be further cleaved at the second loop by enterokinase, resulting in only a small scar after ligation. This protocol adds to the expanding toolbox of genetically‐encoded peptide‐protein chemistry for protein topology engineering. More details are discussed in the article by Zhang et al. on page 113–118.